Thermotropic liquid crystalline 4-(Nonyloxy) benzoic acid: Phase transition temperatures, thermodynamic characterization, and separation of structural isomers - Isik, Birol; Cakar, Fatih; Cankurtaran, Husnu; Cankurtaran, Ozlem (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2023)
The retention behavior of various organic probes on the 4-(Nonyloxy) benzoic acid liquid crystal, which is used as a stationary phase, was investigated using the inverse gas chromatography method at infinite dilution. The thermodynamic parameters including the Flory-Huggins parameter, equation-of-state interaction parameter, the mole fraction activity coefficient, the effective exchange energy parameter, and residual thermodynamic parameters were determined in the temperature range of 423.15-433.15 K by using the retention behavior of the probes on the liquid crystal. It was determined from the thermodynamic parameters that all probes were poor solvents for the liquid crystal. Besides, the results of the 4-(Nonyloxy) benzoic acid liquid crystal was compared with a liquid crystal in the literature, and the effect of the number of alkyl groups on the liquid crystals on the Flory-Huggins interaction parameter and isomer separation was evaluated.
Keywords: 4-(Nonyloxy) Benzoic Acid; Phase Transitions; Liquid Crystal; Inverse Gas Chromatography; Thermodynamic Parameters; Isomer Separation; INVERSE GAS-CHROMATOGRAPHY; 2ND VIRIAL-COEFFICIENTS; POLY(DIMETHYL SILOXANE); ELECTRICAL PARAMETERS; ENTROPY PARAMETERS; EXCHANGE ENTHALPY; STATIONARY PHASES; SYSTEMS; IMPERFECTION; ADSORPTION; Chemistry; Engineering